2013
DOI: 10.1177/2150131913479385
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiologic Analysis of Low Back Pain in Primary Care

Abstract: The study findings revealed that the prevalence of low back pain was higher among women than among men. Low back pain was observed more frequently among older people and among those who were overweight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 26 publications
2
14
1
2
Order By: Relevance
“…Forty-six articles reported occupational standing assessed by self-reports,17 24 26–35 37–50 52–59 61–72 two articles described occupational standing assessed by observations51 60 and two other articles described objectively measured (using accelerometers) occupational standing 25 36. A total of 46 articles reported on samples of workers recruited from a general (not exclusively worker) population and/or a work population,17 24–27 30–47 49–55 57–72 while 4 others reported on data from samples of workers that were recruited through a clinical setting 28 29 48 56. A total of 21 articles reported on random samples drawn from the general (working) population or samples of mixed occupational groups,17 28–30 33 36 37 41 47–49 51 52 54 56 59 62–65 70 and 29 articles reported about specific occupational groups, including healthcare workers,25–27 31 35 38–40 43–45 50 53 57 67 68 71 factory and assembly workers,32 34 60 61 teachers,58 72 farmers,55 69 and construction workers 42…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty-six articles reported occupational standing assessed by self-reports,17 24 26–35 37–50 52–59 61–72 two articles described occupational standing assessed by observations51 60 and two other articles described objectively measured (using accelerometers) occupational standing 25 36. A total of 46 articles reported on samples of workers recruited from a general (not exclusively worker) population and/or a work population,17 24–27 30–47 49–55 57–72 while 4 others reported on data from samples of workers that were recruited through a clinical setting 28 29 48 56. A total of 21 articles reported on random samples drawn from the general (working) population or samples of mixed occupational groups,17 28–30 33 36 37 41 47–49 51 52 54 56 59 62–65 70 and 29 articles reported about specific occupational groups, including healthcare workers,25–27 31 35 38–40 43–45 50 53 57 67 68 71 factory and assembly workers,32 34 60 61 teachers,58 72 farmers,55 69 and construction workers 42…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies reported on significant positive (ie, substantial standing being associated with the occurrence of low-back symptoms) associations,17 25 28 34 39 44 53 67 72 eight studies reported on comparable but non-significant associations,26 29 31 33 38 59 60 69 while in another six studies associations of occupational standing and low-back symptoms were assessed, but the outcomes of these associations were not reported (nor provided by the authors on request) 27 30 35 47 58 61. These studies varied substantially in their definitions for exposure, outcome and exposure–outcome associations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many factors contributing to LBP; however, it is often impossible to determine one specific cause. In a group of adults over 18 years, most people have experienced at least one episode of acute LBP in their lifetime .…”
Section: Introductionmentioning
confidence: 99%
“…People who experience chronic pain have altered movement patterns (van Dieen et al., ; Jacobs et al., ), motor coordination (Hodges and Moseley, ) and the ability to respond to, and compensate for, postural challenges (Hodges et al., ; Jacobs et al., ). Low back pain (LBP) is an extremely common musculoskeletal problem in clinics and it has a huge impact not only on those who suffer it but also on society more widely (Thomsen et al., ; Bener et al., ). In patients with LBP, the negative impact of pain on motor function can be observed; this includes impaired motor control of trunk movements during postural and functional tasks (Hodges et al., ; van Dieen et al., ).…”
Section: Introductionmentioning
confidence: 99%